Answer:
[14] 139
[15] 90
[16] 41
[17] 49
[18] 139
[19] 131
Step-by-step explanation:
[14] Since m ∠ CEB is vertical with m ∠ AED = 139
[15] Knowing that m ∠FBD = 90 degree then m ∠ CEF = 90 degree
[16] Since m ∠ DEB is vertical to m ∠ADC Thus answer = 41
Note: vertical angles are angles opposite each other where two lines cross.
[17] Since m ∠ FED = 90 degree and m ∠ DEB = 41 then 90 - 41 = 49
[18] To Find m ∠CEB we have to subtract from m ∠ DEB
180 - 41 = 139
[19] Knowing that m ∠ FED = 90 degree and m ∠DEB = 41
Then m ∠ AEF = 90 +41=131
<u><em>~Lenvy~</em></u>
4/12 of the fans are kids because 1/4 can be multaplied by 3 to get 3/12
Answer: bisect
<u>Step-by-step explanation:</u>
A segment that is bisected is divided into 2 congruent (equal) lengths from the midpoint.
An angle that is bisected is divided into 2 congruent (equal) angles.
Answer:
41, 34, 105
Step-by-step explanation:
Given that :
Measure of angles :
6x -7; 3x +10; and 10x +25
Recall; sum of angles in a triangle is 180
(6x - 7) + (3x + 10) + (10x + 25) = 180
6x - 7 + 3x + 10 + 10x + 25 = 180
6x + 3x + 10x - 7 + 10 + 25 = 180
19x + 28 = 180
19x = 180 - 28
19x = 152
x = 8
Hence,
6x - 7 = 6(8) - 7 = 41
3x + 10 = 3(8) + 10 = 34
10x + 25 = 10(8) + 25 = 105
Answer:
General solution is
![x = n \pi + \frac{\pi }{8}](https://tex.z-dn.net/?f=x%20%3D%20n%20%5Cpi%20%2B%20%5Cfrac%7B%5Cpi%20%7D%7B8%7D)
Step-by-step explanation:
<u><em>Step(i):-</em></u>
Given cos x - sin x = √2 cos (3 x)
Dividing '√2' on both sides , we get
![\frac{1}{\sqrt{2} } cos (x) - \frac{1}{\sqrt{2} } sin (x) = \frac{\sqrt{2} cos (3 x)}{\sqrt{2} }](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%20%7D%20cos%20%28x%29%20-%20%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%20%7D%20sin%20%28x%29%20%3D%20%5Cfrac%7B%5Csqrt%7B2%7D%20cos%20%283%20x%29%7D%7B%5Csqrt%7B2%7D%20%7D)
we will use trigonometry formulas
a) Cos ( A + B) = Cos A Cos B - sin A sin B
b) ![cos \frac{\pi }{4} = \frac{1}{\sqrt{2} }](https://tex.z-dn.net/?f=cos%20%5Cfrac%7B%5Cpi%20%7D%7B4%7D%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%20%7D)
<u><em>Step(ii):-</em></u>
<u><em></em></u>
<u><em></em></u>
![cos (\frac{\pi }{4} ) cos x - sin(\frac{\pi }{4} ) sin x = cos 3x](https://tex.z-dn.net/?f=cos%20%28%5Cfrac%7B%5Cpi%20%7D%7B4%7D%20%29%20cos%20x%20-%20sin%28%5Cfrac%7B%5Cpi%20%7D%7B4%7D%20%29%20sin%20x%20%3D%20cos%203x)
![cos (\frac{\pi }{4}+x ) = cos 3 x](https://tex.z-dn.net/?f=cos%20%28%5Cfrac%7B%5Cpi%20%7D%7B4%7D%2Bx%20%29%20%3D%20cos%203%20x)
<u><em>Step(iii):-</em></u>
<u><em>General solution of cos x = cos ∝ is x = 2 nπ+∝</em></u>
<u><em>we have </em></u> ![cos (\frac{\pi }{4}+x ) = cos 3 x](https://tex.z-dn.net/?f=cos%20%28%5Cfrac%7B%5Cpi%20%7D%7B4%7D%2Bx%20%29%20%3D%20cos%203%20x)
The general solution of
is
⇒ ![3 x = 2 n \pi + (\frac{\pi }{4}+x )](https://tex.z-dn.net/?f=3%20x%20%20%20%3D%202%20n%20%5Cpi%20%20%2B%20%28%5Cfrac%7B%5Cpi%20%7D%7B4%7D%2Bx%20%29)
⇒ ![3 x- x = 2 n \pi + \frac{\pi }{4}](https://tex.z-dn.net/?f=3%20x-%20x%20%3D%202%20n%20%5Cpi%20%2B%20%5Cfrac%7B%5Cpi%20%7D%7B4%7D)
![2x = 2 n \pi + \frac{\pi }{4}](https://tex.z-dn.net/?f=2x%20%3D%202%20n%20%5Cpi%20%2B%20%5Cfrac%7B%5Cpi%20%7D%7B4%7D)
<em><u>final answer</u></em>:-
General solution is
![x = n \pi + \frac{\pi }{8}](https://tex.z-dn.net/?f=x%20%3D%20n%20%5Cpi%20%2B%20%5Cfrac%7B%5Cpi%20%7D%7B8%7D)